Potensi Beberapa Ikan Sungai Batanghari Sebagai Suplemen Zink bagi Anak dengan Infeksi Saluran Pernapasan Akut (ISPA) - Kurniasih, Dewi; Latifah, Aminahtun; Syarthibi, Ahmad; Andrianto, Dimas; Hafid, Fahmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the zinc content in several types of fish from the Batanghari River as an alternative zinc supplement for children with ISPA. The method used is descriptive analytical to analyzing the results of the zinc level examination and comparing zinc levels in different types of specimens. The results of the research showed that the average zinc content in gabus fish, patin, and lambak was 0.7867 mg/100 gr. The result showed that there is a difference the average zinc content in gabus fish, patin, and lambak (p<0,05) . Keywords: Zinc supplementation; River fish; Acute Respiratory Infection.